2017
DOI: 10.3389/fmicb.2017.01582
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Target slr0946 of the Response Regulator Sll0649 Involving Cadmium Tolerance in Synechocystis sp. PCC 6803

Abstract: Survival of photosynthetic cyanobacteria is challenged by environmental contaminations like heavy metals. Among them, deciphering the regulatory mechanisms for cadmium (Cd) in cyanobacteria would facilitate the construction of Cd-resistant strains. In this study, the DNA-Affinity-Purified-chromatin immunoprecipitation assay was employed to identify the direct targets of Sll0649, which was a Cd2+-related response regulator identified in our previous work in model cyanobacteria Synechocystis sp. PCC 6803. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Finally, Slr0798 is an SmtB-like repressor concerning zinc-transporting P-type ATPase involved in zinc tolerance [ 44 ]. Consistent with the previous study in Synechocystis , overexpression of slr0798 gene with a replicative vector pJA2 could significantly enhance Cd 2+ tolerance [ 23 ]. Unlike SmtB, Slr0798 triggered excess Zn 2+ expulsion by via Slr0798-mediated efflux into the periplasm, which we supposed was the same mode for Cd 2+ .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, Slr0798 is an SmtB-like repressor concerning zinc-transporting P-type ATPase involved in zinc tolerance [ 44 ]. Consistent with the previous study in Synechocystis , overexpression of slr0798 gene with a replicative vector pJA2 could significantly enhance Cd 2+ tolerance [ 23 ]. Unlike SmtB, Slr0798 triggered excess Zn 2+ expulsion by via Slr0798-mediated efflux into the periplasm, which we supposed was the same mode for Cd 2+ .…”
Section: Discussionsupporting
confidence: 89%
“…Wild-type (WT) Synechocystis strain was evolved by serial passaging for 128 passages (802 days) in BG11 medium supplemented with CdSO 4 , as a selective pressure to enrich population with Cd 2+ tolerance. The starting Cd 2+ concentration for WT was set as 4.6 µM as our previous study showed that WT showed a slight growth deficiency at this Cd 2+ concentration level [ 23 ]. Under normal BG11 medium without CdSO 4 , Synechocystis could achieve late exponential phase (OD 750 nm = 1.5) from an initial inoculum (OD 750 nm = 0.1) within 96 h. When CdSO 4 was added, cell growth rate decreased obviously.…”
Section: Resultsmentioning
confidence: 99%
“…For the construction of pJA‐tho‐pilA, the mutated pilA was obtained in the same way. Then the backbone of pJA2‐ Sll0649 (Sun et al ., 2017), the Ptrc‐tho promoter, the T rbcl terminator and the mutated pilA was obtained by primers GG‐PILA‐F and GG‐PILA‐R, GG‐THO‐F and GG‐THO‐R, GG‐TRBCL‐F and GG‐TRBCL‐R, GG‐PJA‐F and‐ GG‐PJA‐R, respectively, and then assembled by golden gate assembly.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the transcriptomics approach, targets for RRs may be identified by measuring protein abundances between WT and mutant strains. Proteomics studies are often accompanied by transcriptomics, metabolomics or ChIP‐seq analyses (Wang et al ., , ; Sepulveda and Lupas, ; Sun et al ., ; Reed et al ., ).…”
Section: Expression Profiling Methodsmentioning
confidence: 98%